ANALISIS KEKUATAN ALAT CETAKAN PANEL DINDING PRECAST - Sukarman; Ega Edistria (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
Walls are non-structural components that function as a barrier between two spaces. Applying walls usually takes a long time and is expensive. However, one of the results of the development of precast concrete technology is panel walls. Currently, there is little innovation in the manufacture of precast wall panel moldings. Wall panel molding motifs are also not widely used. However, problem packages must be made into topics or learning models that involve student participation to support students' problem-based learning (PBL) practices in the Civil Engineering Study Program. This research aims to create a precast wall panel molding tool that meets strength standards and meets market requirements. The stages of this research include the preparation of research materials and collection of reference lists, design of precast wall panel molding tools, strength analysis of precast wall panel molding tools, and manufacture of precast wall panel molding tools. Keywords: molding; precast panel walls